Mechanical analysis for crack-free release of chemical-vapor-deposited diamond wafers - Jeong, JH; Lee, SY; Lee, Wook Seong; Baik, Young Joon; Kwon, D (ELSEVIER SCIENCE SA, 2002)
Chemical-vapor-deposited (CVD) diamond thick films for electronic applications must be released without cracks from the substrate as freestanding wafers. In this study, the mechanism of cracking in the CVD films was investigated experimentally and theoretically. Experimental observations showed that cracks initiated at the edge of the diamond wafer and then propagated towards the center. Finite-element analysis (FEA) reveals that, during cooling, compressive thermal stresses concentrate at the thick film's edge and additional tensile stress acts circumferentially. This was verified by the experimental analysis of diamond films deposited on Si, Mo and W substrates. Observations on low interfacial adhesion and crack-free film on the W substrate indicated that, in addition to the high thermal stress, low interfacial adhesion plays an important role in cracking. Thus, film cracking depends on the fracture strength of the film and its relative magnitude with respect to interfacial adhesion. Methods of crack suppression were suggested on the basis of this cracking mechanism: increase of film thickness and minimization of the substrate's CTE and interfacial adhesion. The analysis was confirmed by successful suppression of cracking by application of a low-adhesion interlayer prior to deposition of diamond film. (C) 2002 Elsevier Science B.V. All rights reserved.